MELIBATKAN SISWA DENGAN TEKS: PEMBELAJARAN KOLABORATIF UNTUK MEMBUKA MAKNA DAN MENDORONG EKSPRESI KREATIF DALAM PENGAJARAN PUISI - Angella Novitaningrum; Fahmy Imaniar; Dea Aulia (Mastery: Master of English Language Journal, 2024)
This study investigates the impact of collaborative learning on student engagement and creative expression in the context of teaching poetry, specifically among fourth-semester English Department students at STIT Miftahul Midad Lumajang. Utilizing a descriptive qualitative research design, the research involved comprehensive observations and semi-structured interviews to gather in-depth insights into students' experiences and perspectives. The findings reveal that collaborative discussions not only foster a deeper understanding of poetic texts but also create a supportive learning environment that encourages students to share diverse interpretations and ideas. Participants reported that engaging with peers enriched their comprehension and inspired them to express their own creativity through poetry writing. Furthermore, the study highlights the significance of peer feedback in refining students' artistic skills, illustrating how constructive interactions enhance their overall learning experience. Ultimately, this research emphasizes the necessity of incorporating collaborative learning strategies in poetry instruction, as such practices not only unlock deeper meanings in literary texts but also cultivate essential skills that prepare students for both academic success and personal growth.